The Existence Of Qonun Jinayah In The National Legislation System - Putra, Ahmad Zidan Muadi; Mardiansyah, Andre; Aryanti, Annisa; Najmudin, Deden (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Legal provisions regarding Regional Regulations and the process of their formation are the basis for the Taqnin process of jinayat law. To understand the mechanisms of criminal law, there are several principles that must be considered in making the Aceh Jinayat Law Qanun. All leaders in the Aceh region showed the process of preparing the Qanun from start to finish. In the Taqnin process in Aceh, the Al-Qur'an and Hadith are the main sources and should not be ignored. Apart from that, the initial plan for the process must be based on the Al-Qur'an and Hadith. Because public legal awareness really determines the success of jinayat law legislation, there are several obstacles in implementing the Aceh Qanun because civil society proposes testing the Qanun, and several organizations even carry out judicial reviews.